Two-electron interference in angular resolved double photoionization of Mg - Sokell, E.; Bolognesi, P.; Kheifets, A.; Bray, Igor; Safgren, S.; Avaldi, L. (Institute of Physics Publishing, 2014)
We observe a two-electron interference effect in the symmetrized amplitude of the resonant double photoionization of Mg which was predicted theoretically, but never before observed experimentally. This observation is based on our experimental study of angle-resolved double photoionization of Mg at the photon energy of 55.49 eV (2p -3d resonance) under equal and unequal energy sharing conditions.